2003
DOI: 10.1089/104303403322124765
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Interleukin-12 Gene Therapy Against Cancer: A Murine Biodistribution and Toxicity Study

Abstract: As a prerequisite for a human clinical trial using interleukin (IL)-12 gene therapy, the biodistribution and safety of IL-12, administered as an intradermal naked DNA injection, was evaluated in mice. The pNGVL3-mIL12 plasmid used in this study is a nonviral vector designed to induce a high level of IL-12 protein expression during a transient transfection of the host cell. The biodistribution was evaluated by a polymerase chain reaction (PCR) assay that is capable of detecting less than 100 copies of the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…In previous murine studies, we were also unable to demonstrate systemic levels of IL-12 at the same dose evaluated in this study. 50 Thus, the lack of detection of IL-12 in blood samples was not unexpected and is consistent with the lack of systemic toxicity we demonstrated in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In previous murine studies, we were also unable to demonstrate systemic levels of IL-12 at the same dose evaluated in this study. 50 Thus, the lack of detection of IL-12 in blood samples was not unexpected and is consistent with the lack of systemic toxicity we demonstrated in this study.…”
Section: Discussionsupporting
confidence: 90%
“…We chose a dose for this clinical trial that was effective with tumors of somewhat similar size in mice, and that was recommended for safety considerations, based on murine safety data and on discussions with the FDA. 50 It is possible that with a higher local dose of IL-12 we would have generated a stronger local effect and may have induced a systemic antitumor effect. We did not measure local IL-12 protein expression to confirm the presence and the amount of gene expression, although this was confirmed in vitro before this study.…”
Section: Discussionmentioning
confidence: 99%
“…A successful anticancer treatment protocol should be one that initiates an extensive, rapid immune response without inducing these toxic side effects. Delivery of IL-12 in the form of gene therapy for melanomas has shown some success without serious adverse side effects (3,4) and has reached clinical trials (5).…”
mentioning
confidence: 99%
“…Imboden et al also reported that there were no abnormalities in organ histology and serum biochemical A B markers in mice administered the recombinant plasmid (pNGVL-3-mIL12) at a dose of 0.5 to 5 ”g. Levels of serum IFN-Îł were also normal, demonstrating that recombinant plasmids containing IL-12 are safe in vivo and could be used in gene therapy (24).…”
Section: Discussionmentioning
confidence: 95%